Fintech Based Peer to Peer Lending: An Opportunity or a Threat? - Titik Setyaningsih; Nugroho Wisnu Murti; Putri Nugrahaningsih (Universitas Muhammadiyah Surakarta, 2019)
One dimension of financial inclusion is people's access to loan funds. Fintech facilitates providers of funds (lenders) with those who need funds (borrowers) through the digital market. Fin Tech Peer-to-peer(P2P) lending has two blades for the borrower's perspective, one side as a solution, on the other hand had a risc. This quantitative research used data with research instruments by questionnaires. Data were analyzed from 62 respondents who lived in around Surakarta in Central Java. This study found that potential customers prefer to use this service rather than not using it, when they perceive that P2P lending is a good opportunity to provide financial needs. More important information needs to be conveyed that the decision to delay using these services has a greater tendency to keep using them in the future. These results provide practical implications that doubts about using Fin Tech-based P2P lending financing services are still high even though prospective customers had good perception about the service as an opportunity from the perspective of the prospective customer. Interesting results also showed that the choice remains consistent even though prospective respondents consider the risk of P2P lending.Keyword: Fin Tech Peer to Peer lending, lender, borrower, apportunity, risk